Molecular Analysis Uncovers the Mechanism of Fertility Restoration in Temperature-Sensitive Polima Cytoplasmic Male-Sterile Brassica napus - Qing Xiao (MDPI AG, 2021)
Temperature-sensitive male sterility is a heritable agronomic trait affected by genotype-environment interactions. In rapeseed (Brassica napus), Polima (pol) temperature-sensitive cytoplasmic male sterility (TCMS) is commonly used for two-line breeding, as the fertility of pol TCMS lines can be partially restored at certain temperatures. However, little is known about the underlying molecular mechanism that controls fertility restoration. Therefore, we aimed to investigate the fertility conversion mechanism of the pol TCMS line at two different ambient temperatures (16 °C and 25 °C). Our results showed that the anthers developed and produced vigorous pollen at 16 °C but not at 25 °C. In addition, we identified a novel co-transcript of orf224-atp6 in the mitochondria that might lead to fertility conversion of the pol TCMS line. RNA-seq analysis showed that 1637 genes were significantly differentially expressed in the fertile flowers of 596-L when compared to the sterile flower of 1318 and 596-H. Detailed analysis revealed that differentially expressed genes were involved in temperature response, ROS accumulation, anther development, and mitochondrial function. Single-molecule long-read isoform sequencing combined with RNA sequencing revealed numerous genes produce alternative splicing transcripts at high temperatures. Here, we also found that alternative oxidase, type II NAD(P)H dehydrogenases, and transcription factor Hsfs might play a crucial role in male fertility under the low-temperature condition. RNA sequencing and bulked segregant analysis coupled with whole-genome sequencing identified the candidate genes involved in the post-transcriptional modification of orf224. Overall, our study described a putative mechanism of fertility restoration in a pol TCMS line controlled by ambient temperature that might help utilise TCMS in the two-line breeding of Brassica crops.